Rasch Model: Analyzing the Items Quality of Mathematics HigherOrder Thinking Skill Instrument - Muhamad Syahidul Qirom; Elah Nurlaelah (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
This research aims to analyse a mathematics HOTS instrument using the Rasch Model to provide a better measurement instrument for mathematics. The result showed, based on Rasch Model analysis, 1) from 20 items, there are only ten items that can be used to measure HOTS of students in mathematics with the difficulty of 3 items being hard and seven items being easy; 2) the reliabilities of the instrument are moderate; 3) the instrument only can divide students into two groups of level ability; and 4) there is no significant differential item functioning (DIF) bias detected on the instrument.